2017
DOI: 10.1021/acsami.7b01735
|View full text |Cite
|
Sign up to set email alerts
|

Light-Up Mitophagy in Live Cells with Dual-Functional Theranostic Phosphorescent Iridium(III) Complexes

Abstract: Phosphorescent Ir(III) complexes are expected to be new multifunctional theranostic platforms that enable the integration of imaging capabilities and anticancer properties. Mitophagy is an important selective autophagic process that degrades dysfunctional mitochondria. Until now, the regulation of mitophagy is still poorly understood. Herein, we present two phosphorescent cyclometalated iridium(III) complexes (Ir1 and Ir2) that can accumulate in mitochondria and induce mitophagy. Because of their intrinsic pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 60 publications
1
51
0
Order By: Relevance
“…The emission maxima of all Ir (III) complexes can be tuned from 474 to 510 nm by varying the type of substituents on P,O‐chelating ligand frameworks. A vibronic structure containing two almost horizontal emission peaks is clearly observed in the emission spectra of these complexes, which indicates that there are noticeable 3 π‐π* LC transitions in the excited states of these complexes . It is possible that the complexes will be quenched in aqueous solution.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…The emission maxima of all Ir (III) complexes can be tuned from 474 to 510 nm by varying the type of substituents on P,O‐chelating ligand frameworks. A vibronic structure containing two almost horizontal emission peaks is clearly observed in the emission spectra of these complexes, which indicates that there are noticeable 3 π‐π* LC transitions in the excited states of these complexes . It is possible that the complexes will be quenched in aqueous solution.…”
Section: Resultsmentioning
confidence: 89%
“…The ligand substituent effect exhibits little variation on these absorption bands. Complexes Ir1 ‐ Ir4 exhibit strong absorption at 250–350 nm due to spin‐allowed 1 π‐π* 1 LC transitions and weak absorption at 350–450 nm assigned to a mixture of 1 MLCT, 1 LLCT, 3 MLCT, 3 LLCT, and 3 π‐π* LC transitions …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Actually, the mitochondrial targeting has various effects on the cell physiology as well as apoptosis. The Mao group recently investigated the biological effects of cyclometalated Ir(III) complexes having a 2,2′‐bisimidazole ligand ( 49 in Scheme ) . They found that the complexes were localized within the mitochondria of A549 cells, eliciting mitochondrial dysfunctions.…”
Section: Theranostic Applicationsmentioning
confidence: 99%